Pengaruh Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian Sepatu Kulit Shoeka Shoes - Zuhriya Choirun Nisa; Andang Fazri; Ade Perdana Siregar (Ebisma (Economics, Business, Management, & Accounting Journal), 2026)
The rapid growth of Indonesia’s domestic market, particularly in goods made from leather, has intensified competition among producers and contributed to a decline in customer satisfaction. Under these conditions, entrepreneurs are required to pay closer attention to several aspects that can shape buyers’ purchasing behavior, especially perceived cost and product excellence. This research was conducted to examine the extent to which consumers’ views on price and product quality affect their decision to purchase Shoeka Shoes.This research adopted a quantitative design supported by a survey technique. Information was gathered through questionnaires distributed to approximately 100 individuals who had experience purchasing Shoeka Shoes products. The participants were selected through purposive sampling, meaning only those who had previously bought the relevant product were included. The collected information was processed using multiple linear regression with the assistance of IBM SPSS Statistics 27. The findings indicate that perceived price and product quality both exert a positive and significant effect on purchase decisions. In this study, consumers were found to be more strongly influenced by price perception than by product quality when deciding to make a purchase. Simultaneously, both variables also showed a meaningful contribution to buying decisions, with a coefficient of determination of about 55.2%. These results suggest that a considerable proportion of consumer purchasing preferences toward Shoeka Shoes can be explained by perceived price and product quality.The outcomes of this study are expected to provide useful insight for business actors, particularly small and medium enterprises in the fashion sector, in increasing product sales through pricing policies that match consumer expectations and through better quality improvement efforts